تصميم ألياف بلورية فوتونية ذات تشتت مسطح جداﹰ - شريتح, إحسان; جعفر, رالدا عبوده (Latakia University Journal -Engineering Sciences Series, 2014)
تعد الاتصالات بالألياف البصرية إحدى الموضوعات التي جذبت الاهتمام بشكل كبير بسبب ميزاتها العديدة ومنها الألياف البلورية الفوتونية التي تتميز بشكل عام بوجود ثقوب هوائية على طولها. ندرس في هذا البحث التشتت اللوني والأطوال الموجية الصفرية لبنيتين مختلفتين لليف البلوري الفوتوني(المثمنة والمربعة), وذلك بعد إضافة ثقوب هوائية صغيرة جداﹰ في القلب (اللب),وتغيير بارامترات البنية بهدف الحصول على تشتت مسطح ومعدوم, وتمت نمذجة هذه البنى للحصول على دليل الانكسار الفعال باستخدام برنامج (Comsol Multiphysics4.2b) ومن ثم حساب التشتت باستخدام برنامج ,(matlabR2011). وقد أظهرت الدراسات السابقة أنه بتغيير بارامترات البنية, كالمسافة بين ثقبين متجاورين وأقطار الثقوب الهوائية في الغلاف, يمكن الحصول على أنواع جديدة من الألياف, مثل الألياف مزاحة التشتت والألياف ذات التشتت المسطح والألياف ذات التشتت المسطح جداﹰ ومعوضات التشتت . ونجعل عامل التشتت اللوني معدوماﹰ عند إضافة ثقوب هوائية صغيرة في القلب بأقطار <!--?mso-application progid="Word.Document"?--> 14dc=0.22خ¼m"> و <!--?mso-application progid="Word.Document"?--> 14dc=0.42[خ¼m]"> لليف المربع و <!--?mso-application progid="Word.Document"?--> 14dc=0.22خ¼m"> و <!--?mso-application progid="Word.Document"?--> 14dc=0.42[خ¼m]"> و <!--?mso-application progid="Word.Document"?--> 14dc=0.82خ¼m"> من اجل الليف المثمن. Optical fiber communication system is a subject of growing interest due to its extremely attractive features. Photonic crystal fibers (PCFs) are one type of optical fiber, it is commonly characterized by a series of air holes that running along the fiber length. In this paper we study the chromatic dispersion and zero dispersion wavelengths(ZDW) between different structures(octangle and square) as we add very small air holes in the center and by changing the parameters of the structure in order to obtain zero or flat dispersion and we model and simulate these structures to calculate the effective refractive index using (Comsol Multiphysics 4.2b) program then calculating the dispersion using (matlabR2011)program. It has been shown that by reshaping the cladding holes, varying the diameters of the holes in one or two rows around the core or changing the refractive index of the holes, different types of specialty fibers can be obtained, such as dispersion shifted fibers (DSFs), non-zero dispersion shifted fibers (NZ-DSFs),dispersion flattened fibers (DFFs), dispersion compensating fibers (DCFs). We made a zero flattened dispersion curve when we add small air holes in the core with diameters <!--?mso-application progid="Word.Document"?--> 14 dc=0.22خ¼m,dc=0.42خ¼m"> for the square fiber and <!--?mso-application progid="Word.Document"?--> 14dc=0.22خ¼m,dc=0.42خ¼m,dc=0.82خ¼m"> for the octangle fiber.